(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1852)
Dr. John Alexander Smith exhibited an antique silver filagree-case and the scissors it held. They were given him to exhibit by a Dr. Stark who also included a note which indicated that these were meant to have belonged to Mary Queen of Scots. Dr. Stark shared the story of its provenance as it was known to him. Dr. Smith concludes that although Mary Queen of Scots’ ownership of the scissors and case could not be corroborated on the strength of the evidence, the workmanship certainly placed it within the right era.